THE EFFECT OF ATTITUDE, SUBJECTIVE NORMS, AND SELF- EFFICACY ON ENTREPRENEURIAL INTEREST WITH ENTREPRENEURSHIP EDUCATION AS A MODERATION IN STUDENTS AT TARUMANAGARA UNIVERSITY - Kent Darren; Andi Wijaya (Graduate Program of Universitas Tarumanagara, 2026)
Unemployment remains one of the major economic issues in many countries, including Indonesia. One strategic approach to reducing unemployment and fostering job creation is through entrepreneurship development, which can be strengthened through entrepreneurship education. This study aims to examine the effects of Attitudes, Subjective Norms, and Self-Efficacy on Entrepreneurial Interest, with Entrepreneurship Education serving as a moderating variable among students at Tarumanagara University. A total of 135 respondents from the Management and Accounting departments participated in this study. Data were processed using SmartPLS 4 software. The results indicate that Attitudes, Subjective Norms, and Self-Efficacy positively and significantly influence Entrepreneurial Interest. Nevertheless, Entrepreneurship Education does not moderate the relationships between these three variables and Entrepreneurial Interest.